The Role of Environmental and Geographical Factors in the Education Process - Gul Mazloum Yar, Fayaz; Ishaq Shaheedzooy, Mohammad (Journal of World Science, 2023)
Throughout history, humans have learned and acquired knowledge from their surroundings. The importance of a suitable and standardized educational environment for effective learning and teaching is widely acknowledged. The educational environment significantly affects students' learning processes, necessitating a thorough understanding of the environmental and geographical factors that impact it. This Research aims to investigate the role of environmental and geographical factors in the educational process. It seeks to explore how these factors influence learning outcomes and analyze the factors contributing to the creation of optimal educational spaces. The research employs a comprehensive methodology to examine the impact of environmental and geographical factors on the educational process. It focuses on studying children's behavioral patterns in educational environments, with particular attention to elements such as classroom size and lighting. The research findings highlight the significance of environmental and geographical factors in shaping the learning process. Specifically, factors like classroom size and lighting have been identified as crucial elements that enhance learning outcomes. The study emphasizes the importance of creating educational environments that cater to learners' needs. By considering environmental and geographical factors, such as classroom size and lighting, educators can design optimal learning spaces. The findings underscore the necessity of improving the structure of education to foster the physical, mental, emotional, and social development of students.